Treatment of Methylene Blue Using Ni-Al/Magnetite Biochar Layered Double Hydroxides Composite by Adsorption - Zahara, Zaqiya Artha; Royani, Idha; Palapa, Neza Rahayu; Mohadi, Risfidian; Lesbani, Aldes (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Methylene blue dye is hard to degrade and requires treatment using Ni-Al Layered double hydroxides (LDHs) modified with magnetite biochar (MBC) to form Ni-Al/magnetite biochar composite in overcoming environmental pollution. Material attainment was identified by characterization using X-Ray Diffraction (XRD), Fourier Transform – Infra Red (FT-IR), Branuer Emmet Teller (BET), Scanning Electron Microscopy – Energy Dispersive X-Ray (SEM-EDX) and Vibration Sample Magnetometer (VSM). XRD characterization displays angle 2θ at 11°, 60° is a typical angle of LDH, and angles 22° and 35° of magnetite biochar. FT-IR characterization analysis at wavelength 1381 cm-1 for NO3- group and M-O group at wave number 700 cm-1. C-H group on biochar at 1404 cm-1 and wave number 586 cm-1 for Fe-O group. BET characterization analysis of Ni-Al/MBC has a large surface area and pore volume of 127.310 m²/g and 0.1950 cm³/g. SEM characterization analysis of Ni-Al/MBC has large, coarse pores and non-uniform shape, EDX data shows that there are forming elements such as Ni, Al from LDH and, Fe, C elements from magnetite biochar. pH, kinetics, isotherms, and thermodynamics become influential in adsorption processes. The adsorption capacity of the composite reaches 68.493 mg/g by following the Langmuir equation and adsorption kinetics refers to the Pseudo Second Order (PSO) equation. Adsorption continuity is spontaneous and endothermic. Ni-Al/MBC has stability in the process of adsorbent regeneration up to five adsorption cycles and, therefore can be used as a potential adsorbent in the treatment of methylene blue dye in aqueous environmental pollution. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).